Evaluation of oral hygiene in school children from the eastern region of Wielkopolska - Matthews-Brzozowska, Teresa; Sikorska, Agnieszka; Cieślik, Kornela; Głowacka, Arleta; Matthews-Kozanecka, Maja (Journal of Medical Science, 2016)
Aim. The aim of the study was to assess oral health in school-age children on the basis of subjective and objective judgement, based on selected indicators. Material and Methods. The study included students aged 10–13 years of primary and junior-high schools in the Mid Eastern region of Wielkopolska. Oral hygiene assessment was based on a prepared subjective questionnaireas well as on the basis of indicators: API P1.I, GI, including the sex of children. Results. Of the 161 children of school age, most of them, as many as 145 showed attention to oral health, brushing teeth twice a day; some of them apply additional measures for oral hygiene – 39 children. In both sexes there were no deviations indicators examined. Between gender showed no difference, as confirmed statistically. Conclusions. Oral hygiene in children with high health awareness rated positively, it should be emphasized that despite noninvasiveness the research group of respondents accounted for a small percentage of the children invited to the study, which points the need to undertake educational activities on a larger scale.